Reposisi Pemberian Kuasa Dalam Konsep “Volmacht Dan Lastgeving” Berdasarkan Cita Hukum Pancasila - Latumeten, Pieter E. (Jurnal Hukum & Pembangunan, 2017)
The dynamic development of mandate as a contract that brings forth representation is disaccord with the definition and norm of lastgeving under Indonesian Civil Code. This research has a goal to unravel such issue by pointing out of that there is a need for repositioning in the form concept renewal for the definition and norm of mandate contract under Indonesian Civil Code that is line with our philosophical foundation (rechtsidee), which is Pancasila. Juridical normative methodology carries out of the repositioning by examining the principles, its own concept as a postivie law and meta juridical, and with the help of comparative law, lastgeving and volmacht can be clarified by compaing the two terms and its rules under Indonesian Civil Code and Dutch Law.